A Model to Study Myelinated Fiber Degeneration and Regeneration in Human Skin. Issue 3 (6th January 2020) - Provitera, Vincenzo; Piscosquito, Giuseppe; Manganelli, Fiore; Mozzillo, Stefania; Caporaso, Giuseppe; Stancanelli, Annamaria; Borreca, Ilaria; Di Caprio, Giovanni; Santoro, Lucio; Nolano, Maria
Abstract : Objective: To describe morphological changes associated with degeneration and regeneration of large fibers in the skin using a model of chronic compression of the median nerve. Methods: We studied cutaneous innervation in 30 patients with chronic compression of the median nerve at the wrist. Before surgery, we assessed the symptom severity and performed neurography, quantitative sensory testing, and analysis of nerve morphology and morphometry in skin biopsies from the third digit fingertip. Fifteen patients repeated all tests 12 months after the surgery. Thirty age‐ and sex‐matched healthy subjects were included in the study. Results: Clinical and neurophysiological basal assessment showed a moderate involvement of the median nerve. Quantitative sensory testing showed abnormal findings. The density of intraepidermal nerve fibers and intrapapillary myelinated endings was reduced. Myelinated fibers showed caliber reduction and nodal elongation. Meissner corpuscles had normal density but were located deeper in the dermis and their capsule appeared partially empty. During follow‐up, patients exhibited a positive clinical and neurophysiological outcome. Quantitative sensory testing improved. Intraepidermal nerve fibers and intrapapillary myelinated endings remained unchanged, but the caliber of intrapapillary myelinated endings was increased. The neural component of the Meissner corpuscle filled the capsule of the mechanoreceptors that remained deeper in the dermis. The position of vasoactive intestinal peptide–immunoreactive fibers was more superficial compared to the basal assessment and controls. Interpretation: We recognized and quantified the pathological changes associated with nerve degeneration and regeneration in skin and proposed new parameters that may increase the diagnostic yield of skin biopsy in clinical practice. Ann Neurol 2020;87:456–465